Impact of Internal and External Factors of a Company Facing the Return of the Company with a Compas100 Indeks Noted on the Indonesia Shipping Borse - Sinaga, Uchock Pandapotan Raja Salomo; Rudianto, Dudi (Yayasan Ilomata, 2024)
The coal industry is a pillar of the Indonesian economy as the main energy source and an important contributor to the country's foreign exchange. Coal companies in the Kompas100 Index show significant stock performance measurements, giving rise to the need to understand the factors that contribute to variations in stock returns, both in terms of internal and external factors. This research aims to analyze the influence of internal factors (Current Ratio, Net Profit Margin, Debt to Equity Ratio) and external factors (inflation, interest rates, currency exchange rates) on stock returns of coal companies listed on the Kompas100 Index on the Indonesia Stock Exchange. This research method uses a quantitative approach, purposive sampling is used to select samples based on the availability of complete financial data and relevant historical stock price data. The analysis shows that in this study, the Current Ratio (CR) has a significant positive influence on Stock Returns, while the Net Profit Margin (NPM) also has a significant positive influence. On the other hand, the Debt to Equity Ratio (DER) has a significant positive influence. Externally, inflation has a significant negative impact on Stock Returns, while interest rates also have a significant negative impact, but the exchange rate does not affect Stock Returns. Overall, internal factors influence Stock Returns, and external factors also influence Stock Returns. Additionally, the combination of internal and external factors collectively affects Stock Returns with significant interaction complexity.